Analisis Efektivitas Penerapan Sistem Pengendalian Intern Pemerintah Guna Peningkatan Kinerja Instansi Pemerintah pada Inspektorat Daerah Kabupaten Garut - Alya Rihhadatulaisy Mufidah; Yanti Rufaedah; Sugih Sutrisno Putra (Indonesian Accounting Research Journal, 2023)
This study aims to determine whether the application of the Government Internal Control System at the Regional Inspectorate of Garut Regency is effective in supporting agency performance. The more effective the implementation of the internal control system, the better the performance of government agencies. The method used in this research is qualitative method. by using primary data in the form of interviews with sources from the Regional Inspectorate of Garut Regency and secondary data in the form of relevant documentation. Test the validity of the data used in this study, namely the credibility test (credibility), transferability (transferability), reliability test (dependability), and objectivity test (confirmability). Data analysis techniques used are data collection, data reduction, data presentation and conclusion. The results showed that the application of the Government's Internal Control System at the Regional Inspectorate of Garut Regency had effectively supported the performance of the Inspectorate Agencies. It is hoped that this research can be useful as learning material regarding the Effectiveness of SPIP implementation in order to increase Institutional Performance.